2019
DOI: 10.33225/jbse/19.18.907
|View full text |Cite
|
Sign up to set email alerts
|

The Impacts of a Marine Science Board Game on Motivation, Interest, and Achievement in Marine Science Learning

Abstract: of the dimensions including 'memory ' , 'understanding' , 'high-level thinking' , and 'total score' were significantly different between the two groups.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 12 publications
(14 reference statements)
0
5
0
Order By: Relevance
“…The 5E model is widely used in science education worldwide and even at the national strategic level (National Research Council, 2006). A bulk of case studies have demonstrated that, compared with traditional approaches, the 5E model enables students to achieve more outstanding achievements in three areas: scientific reasoning (Siwawetkul and Koraneekij, 2018; Susilowati and Anam, 2017), mastery of the subject (Gillies and Rafter, 2020; Lin et al ., 2019a), and interest and attitude toward science (Hew et al ., 2016; Lin et al. , 2019b).…”
Section: Literature Reviewmentioning
confidence: 99%
“…The 5E model is widely used in science education worldwide and even at the national strategic level (National Research Council, 2006). A bulk of case studies have demonstrated that, compared with traditional approaches, the 5E model enables students to achieve more outstanding achievements in three areas: scientific reasoning (Siwawetkul and Koraneekij, 2018; Susilowati and Anam, 2017), mastery of the subject (Gillies and Rafter, 2020; Lin et al ., 2019a), and interest and attitude toward science (Hew et al ., 2016; Lin et al. , 2019b).…”
Section: Literature Reviewmentioning
confidence: 99%
“…According to preliminary studies, the level of interest affects students’ learning motivation [ 15 , 54 ], self-efficacy [ 55 ], self-regulation, and overall outcomes [ 56 , 57 ]. Students need to learn and analyze the relationship between stress and teacher and parent support, especially in mathematics.…”
Section: Literature Reviewmentioning
confidence: 99%
“…In the Instructional Process section, the teacher can direct students to define the concept of function. The use of learning technology can increase students' interest in learning and changing the classroom atmosphere (Hsu, 2015;Khine et al, 2017;Lin, Huang, & Chang, 2019;Newhouse, 2017). Technology also enhances the student experience (Akbulut et al, 2020;Maeng, Mulvey, Smetana, & Bell, 2013;Suweken, 2018;Voithofer, Nelson, Han, & Caines, 2019;Yang et al, 2017).…”
Section: Instructional Processmentioning
confidence: 99%